5(2x-5)+3=4(-5x+2)-7x

Simple and best practice solution for 5(2x-5)+3=4(-5x+2)-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-5)+3=4(-5x+2)-7x equation:



5(2x-5)+3=4(-5x+2)-7x
We move all terms to the left:
5(2x-5)+3-(4(-5x+2)-7x)=0
We multiply parentheses
10x-(4(-5x+2)-7x)-25+3=0
We calculate terms in parentheses: -(4(-5x+2)-7x), so:
4(-5x+2)-7x
We add all the numbers together, and all the variables
-7x+4(-5x+2)
We multiply parentheses
-7x-20x+8
We add all the numbers together, and all the variables
-27x+8
Back to the equation:
-(-27x+8)
We add all the numbers together, and all the variables
10x-(-27x+8)-22=0
We get rid of parentheses
10x+27x-8-22=0
We add all the numbers together, and all the variables
37x-30=0
We move all terms containing x to the left, all other terms to the right
37x=30
x=30/37
x=30/37

See similar equations:

| 3x+2x-5=8x-10-2x | | 5x-35=7x-5 | | 3(0)-14y=8 | | 4x—3=x | | w+1.63=6.44 | | 6x-5=7x-4 | | 12,655=x2+15x+55 | | 22x-6=48 | | -5x+15=225 | | 7/3w=35 | | 2n=210 | | 4f=-10−f | | 2n=210= | | -2(v+5)=6v-26 | | -15=3x-7x=-43 | | -0.6f=+2.26 | | 5(8+8)=2x-7+8(x-1) | | 5+6a+102=180 | | 2n=212 | | 2(1+1.5b)=3b+2 | | -8=-8v+4(v-5) | | 8z+3=-21 | | 124+(4x-7)+(7x-25)=180 | | s/2-6=2 | | n/5-5=5 | | x=1/2(74-58) | | 7n+2=5×6 | | 2.6=y/2.4 | | x=1/2(58+74) | | 6(y+4)=18 | | 2.4=x/3.7 | | 112+(x+22)+(11x-2)=180 |

Equations solver categories